Under the influence: exogenous testosterone influences men’s cross-sex perceptions of sexual interest - Goetz, Stefan M. M.; Lucas, Todd; Carré, Justin M. (Frontiers in Psychology, 2024)
The sexual misperception bias is a cognitive bias in which men tend to overestimate sexual interest from women, potentially shaped by evolutionary mating strategies. Testosterone, often linked to mating behaviors, might play a role in sustaining sexual overperceptions. To explore this possibility, we conducted a placebo-controlled study with 190 heterosexual men, administering either 11 mg of testosterone or a placebo. Participants interacted with an attractive female confederate, while naïve raters assessed the confederate’s affiliative behaviors. Our findings suggest that exogenous testosterone did not broadly impact sexual overperception. However, we found that affiliative behavior from the confederate was positively correlated with perceived sexual interest among testosterone-treated, but not placebo-treated men. In addition, we found that this effect among testosterone-treated men was contingent on their self-perceived attractiveness. Specifically, the confederate’s affiliative behaviors were positively correlated with perceived sexual interest, but only for testosterone-treated men with average or above average self-perceived attractiveness. Furthermore, our data revealed that men’s tendency to project their own short-term and long-term mating interests increases as a function of self-perceived attractiveness, and this coupling is enhanced by testosterone for long-term interest. Taken together, these results suggest that testosterone may potentiate existing biases, particularly when sexual motivation is high, and bias perceptions of friendly behavior when engaging in cross-sex mindreading. This study adds to the understanding of the neuroendocrine bases of social cognition, suggesting that testosterone can affect men’s perceptions of potential mates.